Biological nanopore approach for single‐molecule analysis of nucleobase modifications - Pengrui Lv; Yongyi Yang; Shuang Li; Cherie S. Tan; Dong Ming (Electrochemical Science Advances, 2022)
Abstract Base modifications play an essential role in cellular function, and the abnormal expressions of base modifications are associated with numerous diseases. Unfortunately, existing detection methods have difficulty obtaining sequence information of various modified nucleobases at the single‐molecule resolution. Label‐free single‐molecule sequencing technology using biological nanopores can direct sequence canonical nucleobases. However, the discrimination of hundreds of noncanonical nucleobase modifications at the single‐molecule resolution is still challenging. In this minireview, we introduced the recent advances in detecting nucleobase modifications using biological nanopores from nucleic acid translocation controlling, confinement effects on nucleobase discrimination, and applications of nanopore sequencers for modification detection.